The Influence of the Project Based Learning Model on Student Learning Outcomes and Learning Activities in the Ecosystem Topic - Veronika Sijabat; Adriana (UNIVERSITAS PGRI MADIUN, 2026)
This research aims to determine the influence of the Project Based Learning model on student learning outcomes and activities in the ecosystem topic. The research employed a quasi experimental design with a pretest post-test control group design. The subjects consisted of two classes: the experimental class, which was taught using the PjBL model, and the control class, which was taught using the inquiry model. The research instruments included a multiple-choice learning outcome test and an observation sheet for students learning activities. The results showed that the average pretest score of students in the experimental class was 44.68, which increased to 80.42 in the post-test, while the control class increased from 43.34 to 75.57. The results of the independent sample t-test indicated a significant difference between the two classes (Sig. 0.001 < 0.05). Students learning activities in the experimental class were also higher, with an average percentage ranging from 61.49% to 67.51% (active category), compared to the control class, which ranged from 55.39% to 62.15% (fairly active to active category). Based on these findings, it can be concluded that the implementation of the Project Based Learning model has a positive effect on students learning outcomes and learning activities in ecosystem material. Therefore, this model can be considered an effective alternative to improve conceptual understanding and students active participation in biology learning.